Prevalence of Visual Disturbances in Patients with Chronic Rhinosinusitis: A Cross-sectional Study - Syed Ahmad Hassan Waqas Subzwari, Sidra Shakil, Hafiz Syed Umar Abdur Rehman, Abdul Sattar, Saira Bano, Abdul Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic rhinosinusitis (CRS) is an underacknowledged chronic inflammatory disease of the paranasal sinuses with a systemic impact. Because the sinuses are anatomically close to the orbital structures, CRS can cause visual disturbances. This is, however, not well recognized among visual complications in CRS, especially in countries such as Pakistan. Aims and Objectives: The purpose was to assess the prevalence and clinical pattern of visual disturbances in patients with chronic rhinosinusitis, and to identify the possible association with CRS subtypes and radiologic severity. Methodology: The study was conducted as a cross-sectional study at the Allied hospital II , Faisalabad, Pakistan from June 2022 to May 2023. A total of n=50 adult patients with clinically and radiographically confirmed CRS were enrolled. Demographic data, CRS type, duration of symptoms, and CT-based Lund Mackay scores were recorded. The complete ophthalmologic assessment was performed on each patient. The data were statistically analyzed with SPSS version 26, set at p < 0.05. Results: Of 50 patients, 15 (30%) had visual disturbance. Complaints were blurred vision (46.7%), diplopia (26.7%), and retro-orbital pain (20%). It was seen in 6% of patients that optic disc edema and in 8% that decreased visual acuity. Visual disturbances were found to be statistically associated with CRS with nasal polyps (p = 0.041). There were trends toward association with higher Lund-Mackay scores and longer disease duration, but they did not reach statistical significance. Conclusion: Relatively common visual symptoms occur in CRS, particularly in patients with nasal polyps and extensive sinus involvement. Early identification through multidisciplinary evaluation is necessary to prevent possible irreversible ocular complications. In high-risk patients, integration of CRS management protocols should include regular ophthalmologic screening. Keywords: Chronic rhinosinusitis, visual disturbances, nasal polyps, blurred vision, optic disc edema, ophthalmologic complications, Lund-Mackay score, Pakistan